2008
DOI: 10.2459/jcm.0b013e3282f2197f
|View full text |Cite
|
Sign up to set email alerts
|

Changes in left atrial dimension and function and left ventricular geometry in newly diagnosed untreated hypertensive subjects

Abstract: Changes in the geometry of the left ventricle occur early in hypertension and precede deterioration in left ventricular systolic function. The corresponding left atrial changes are marginal and are indicative of increased left atrial length and accentuated atrial systolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Changes in the left ventricle (LV) under the effects of hypertension are well studied including LV hypertrophy, abnormal geometry, and diastolic dysfunction [1]. The left atrium (LA) is also affected by hypertension and LA enlargement is noted even earlier in mild hypertension [2].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the left ventricle (LV) under the effects of hypertension are well studied including LV hypertrophy, abnormal geometry, and diastolic dysfunction [1]. The left atrium (LA) is also affected by hypertension and LA enlargement is noted even earlier in mild hypertension [2].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the authors evaluated left atrial structural and functional alterations in hypertension which was found to be statistically different compared to age and sex-matched apparently normal individuals [140] .…”
Section: Left Ventricular Diastolic Dysfunctionmentioning
confidence: 99%
“…Compared to their age-and sex-matched controls, hypertensive Africans show statistically significant left atrial structural and functional alterations [21].…”
Section: Atrial Function and Dysfunctionmentioning
confidence: 97%
“…Absolute and indexed left atrial diameter, area, or volume is increased in African hypertensive subjects [20,21]. Compared to their age-and sex-matched controls, hypertensive Africans show statistically significant left atrial structural and functional alterations [21].…”
Section: Atrial Function and Dysfunctionmentioning
confidence: 99%